Twitter Blue Tick - A Study of its Impact on Society - Barsaiyan, Sunil; Sijoria, Charu (Indian Journal of Marketing, 2021)
The Twitter account verification badge or popularly known as â€œblue tick,â€ is the most in-demand feature. Twitter calls it an authentication sign, not the endorsement, and as per policy, it can be assigned only to the accounts of public interest. Still, it is an aspiration for many users, and many discussions keep happening around it. In this paper, a systematic review of academic and industry literature was done to study the user understanding and aspiration for the blue tick badge, its impact on the users and society at large, and the platformâ€™s policy to award them. Results showed that the blue tick is the â€œstatus symbolâ€ for Twitter users, and accounts with this badge are considered elite and influencers. This perception for blue ticks is not sentimental but has been crafted by the platform by keeping its supply low and restricted to famous account owners. Also, the study highlighted that there are no specific and clear guidelines on Twitterâ€™s end for account verification and disproof. As a result, the platform comes at the center of controversy and public ire on several occasions. The results of the study also contribute towards building theory and drawing managerial implications for industry practitioners. This study is unique as no past research has been conducted to deep dive into the blue tick ecosystem, though it is one of the most talked-about topics on the internet.